The Impact of the Qur’anic Verses in Clarifying the Descriptions of the Best of Creation (Journal of the College of Basic Education, 2024)
This research falls within the studies of objective interpretation, and is related to the unity of the vocabulary that described descriptions of the Prophet in the Meccan and Medinan eras, and they are woven with sophisticated rhetorical subtleties. Its knots were arranged in response to the extent of the influence of these verses in clarifying the descriptions of the Prophet, may God bless him and grant him peace, with the aim of clarifying their concept and miraculousness in their context, and their behavioral outcomes for the Muslim. It adopted the inductive and descriptive-analytical approaches, and built it on a preface in which I explained the concept of the Qur’anic verses and their types, and four demands; The first came in the actual Qur’anic verses explaining the Prophet’s existential descriptions, the second in the derived Qur’anic verses explaining the Prophet’s existential descriptions, the third in the derived Qur’anic verses explaining the Prophet’s nihilistic descriptions, and the fourth in the effect of the Qur’anic verses in forming a picture of the apostolic biography. I concluded that the total of these unique items amounted to thirteen scrap gems. Ten of them are existential, distributed equally between derivatives and verbs, and three of them are nihilistic derivatives. It was colored by the eyes of rhetoric in the Qur’anic use of it, and some of them were noticed by a group of ancient commentators, among which I expanded its graphic capacity and conveyed to it subtle connotations that sunk into the depth of taste, and that the Muslim is addressed by its conceptual dimensions according to his assignment. The research recommends including the Qur’anic meanings in the topics of Qur’anic sciences, reporting them in academic studies, and compiling a reference book for them that addresses them from their various dimensions.